Motivational interviewing to improve self‐care in heart failure patients (MOTIVATE‐HF): a randomized controlled trial - Ercole Vellone; Paola Rebora; Davide Ausili; Valentina Zeffiro; Gianluca Pucciarelli; Gabriele Caggianelli; Stefano Masci; Rosaria Alvaro; Barbara Riegel (ESC Heart Failure)
Abstract Aims Self‐care, an essential component of heart failure (HF) treatment, is inadequate in most patients. We evaluated if motivational interviewing (MI) (i) improves patient self‐care maintenance (primary endpoint; e.g. taking medications), self‐care management (e.g. responding to symptoms) and self‐care confidence (or self‐efficacy) 3 months after enrolment; (ii) changes self‐care over 1 year, and (iii) augments patient self‐care if informal caregivers are involved. Methods and results Parallel randomized controlled trial (1:1:1). A sample of 510 patients (median 74 years, 58% male) and caregivers (median 55 years, 75% female) was randomized to Arm 1 (MI only for patients), Arm 2 (MI for patients and caregivers), or Arm 3 (usual care). The intervention in Arms 1 and 2 consisted of one face‐to‐face MI session with three telephone contacts. Self‐care was evaluated with the Self‐Care of HF Index measuring self‐care maintenance, management, and confidence. Scores on each scale range from 0 to 100 with higher scores indicating better self‐care; ≥70 is considered adequate. At 3 months, self‐care maintenance improved 6.99, 7.42 and 2.58 points in Arms 1, 2, and 3, respectively (P = 0.028). Self‐care maintenance was adequate in 18.4%, 19.4%, and 9.2% of patients in Arms 1, 2 and 3, respectively (P = 0.016). Over 1 year, self‐care maintenance, management, and confidence scores in Arms 1 and 2 were significantly higher than in Arm 3 in several follow‐ups. Over 1 year, Arm 2 had the best scores in self‐care management. Conclusions MI significantly improved self‐care in HF patients. Including caregivers may potentiate the effect, especially in self‐care management. ClinicalTrial.gov, identifier: NCT02894502.